A framework for the examination of urban coastal areas against the risk of sea level rise and evaluation of design strategies: The cases of Izmir and Thessaloniki - Ercanlı Çağla (E3S Web of Conferences)
The aim of the study is to provide a framework for determining design and adaptation strategies for urban coastal area uses against sea level rise risk due to climate change. The main argument of the study is that strategies to be put forward at the scale of urban design and architecture are important in preventing the negative effects of sea level rise and common and developing strategies can be created for cities with similar urban morphologies, spatial and functional characteristics. Within this scope, Izmir and Thessaloniki cities are chosen as a case that have morphologically and spatially/functionally similar characteristics. In the research part, analysis parameters for the characteristics of urban coastal areas are grouped as; geographical/morphological and spatial/functional. According to these two parameters, possible impacts, also design and adaptation strategies in literature are classified in urban and architectural scales. In the case study, coastal area sections of cities were prepared to understand the morphological and spatial/functional characteristics. Then, sections were divided into sub- segments to understand urban space structures. Strategies includes suggestions for reorganizing urban space functions, designing urban landscapes, urban equipment and furniture, also creating infrastructure decisions and strengthening the existing building stock in the short term for flood risk.